The role of ethnicity and social capital in immigration to Hungary - Ireń God̈ri (Hungarian Demographic Research Institute, 2010)
The paper examining a particular segment of Hungarian immigration - which, at the same time, most powerfully determines the overall trend of immigration - explores the presence and role of migrants' personal ties and the resources available through these. The aim of the paper is to present the immigration process to Hungary from neighbouring countries utilising a network perspective and to reveal the role of social capital during migration in a case when most of the immigrants are of the same ethnicity as the receiving population, and thus - contrary to other immigrant groups - ethnic capital is also present in the process. The paper first outlines the present context of the immigration process, as well as its historical background, highlighting the manifestations of its ethnic character to the present day. Next, we briefly review the way in which the network approach appears in migration research and we sum up its most important theoretical results. Then we provide a detailed description of the questions examined, the methods applied and the variables involved in the analysis. This is followed by the analysis of the empirical data exploring the personal ties that immigrants had with the target country before their immigration and the resources (information, help) they were able to mobilize through this. Finally, we summarize the most important results and draw the conclusions.
Keywords: J61; 300; Familienplanung; Fertilität; Vergleich; Niederlande; Schweiz; Ungarn; Bulgarien